Current Foreign Studies of Professional Burnout in Teachers - Kochetkov, N.V.; Marinova, T.Y.; Orlov, V.A.; Raskhodchikova, M.N.; Haymovskaya, N.A. (Sovremennaâ Zarubežnaâ Psihologiâ, 2023)
The article is aimed at the analysis of modern foreign publications devoted to the professional burnout of school teachers. It was shown that the vector of research by psychologists is focused at studying the current level of teacher burnout, various correlates of burnout, the impact of the consequences of the COVID-19 pandemic on this process, as well as the prophylaxis and prevention of burnout. It can be argued that the globally recognized approach to burnout is the approach of K. Maslak, and the theory that is gaining popularity in terms of which teachers' burnout is explained as the theory of "work requirements and resources". Based on empirical data, it can be stated that the prevalence of burnout among teachers is up to 30%, and the average percentage of high burnout is about 10%. One of the most significant factors of burnout is thought to be the behavior of students, as well as bureaucracy. Also, the key factors influencing burnout include self-efficacy, social support, feedback from the subjects of the educational process, emotional work, lack of opportunity to learn and make decisions independently. At the same time, the inconsistency of the available empirical data is notable, which can be explained by the difference in the applied methodology and research methods. Among the methods of practical work with the phenomenon of professional burnout, there are those that are based on the practices of awareness and the cognitive-behavioral approach. Статья направлена на анализ современных зарубежных публикаций, посвященных профессиональному выгоранию у школьных учителей. Было показано, что вектор исследований психологов направлен на изучение текущего уровня выгорания у учителей, различных коррелятов выгорания, влияния на этот процесс следствий пандемии COVID-19, а также на профилактику и предотвращение выгорания. Можно утверждать, что общепризнанным во всем мире подходом к выгоранию является подход К. Маслак, а набирающей популярность теорией, в рамках которой объясняется выгорание у учителей, - теория «рабочих требований и ресурсов». Исходя из эмпирических данных можно констатировать факт того, что распространенность выгорания у учителей составляет до 30%, а средний процент высокого выгорания - около 10%. Одними из наиболее весомых факторов выгорания можно считать поведение учащихся, а также бюрократию. Также к ключевым факторам, влияющими на выгорание, относят самоэффективность, социальную поддержку, обратную связь от субъектов образовательного процесса, эмоциональный труд, отсутствие возможности обучаться и самостоятельно принимать решения. При этом можно отметить противоречивость имеющихся эмпирических данных, что можно объяснить различием в применяемой методологии и методах исследования. Среди методов практической работы с феноменом профессионального выгорания выделяют те, которые базируются на практиках осознанности и когнитивно-бихевиоральном подходе.